2021
DOI: 10.1094/mpmi-12-20-0339-r
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Genomic Compartments with Contrastive Modes of Functional Losses of Host Specificity Determinants During Pathotype Differentiation in Pyricularia oryzae

Abstract: The specificity between pathotypes of Pyricularia oryzae and genera of gramineous plants is governed by gene-for-gene interactions. Here, we show that avirulence genes involved in this host specificity have undergone different modes of functional losses dependent on, or affected by genomic compartments harboring them. The avirulence of an Eleusine pathotype on wheat is controlled by five genes including PWT3 which played a key role in the evolution of the Triticum pathotype (the wheat blast fungus). We cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Using chromosome-level, reference-guided genome assemblies, we first determined that the correct chromosomal position for PWT6, and the corresponding null locus, is in the middle of chromosome 5 (fig. S8A), and not the end of chromosome 3 as originally reported (47). A quick inspection of PoL1's haplotype at this locus told us that the donor was probably the PoU1 parent and, consistent with this prediction, all PoU1 isolates were found to lack PWT6.…”
Section: Sequential Admixture Drove Broad Infection Capability On Wheat Through Multiple Independent Contributions Of Null/non-functionalsupporting
confidence: 57%
See 3 more Smart Citations
“…Using chromosome-level, reference-guided genome assemblies, we first determined that the correct chromosomal position for PWT6, and the corresponding null locus, is in the middle of chromosome 5 (fig. S8A), and not the end of chromosome 3 as originally reported (47). A quick inspection of PoL1's haplotype at this locus told us that the donor was probably the PoU1 parent and, consistent with this prediction, all PoU1 isolates were found to lack PWT6.…”
Section: Sequential Admixture Drove Broad Infection Capability On Wheat Through Multiple Independent Contributions Of Null/non-functionalsupporting
confidence: 57%
“…Prior work has shown that successful infection of wheat requires the loss or inactivation of the PWT6 and PWT3 host-specificity genes that would normally trigger resistance in wheat containing the corresponding resistance genes ( 29, 47 ). Therefore, we sought to understand the dynamics of these genes in the context of PoT/PoL evolution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevailing model for WB evolution holds that it involved sequential loss/mutation of key host specificity genes, which allowed an Eleusine pathogen to jump hosts-first onto Lolium, then onto wheat lacking the RWT3 resistance gene and, finally, onto RWT3 wheat 32,33 . However, this could not explain how such high levels of genetic diversity arose in a population that had no obvious existence before 1985.…”
mentioning
confidence: 99%